Crack identification in beam by antiresonant frequencies - Khiem, Nguyen Tien; Tuan, Nguyen Minh; Lien, Pham Thi Ba (Vietnam Journal of Mechanics, 2021)
The present paper deals with the concept of antiresonance in multiple cracked beams and application for multi-crack identification. First, governing equations for antiresonant frequency are conducted and used for both computing antiresonant frequencies versus crack parameters and measuring-loading colocation and identifying cracks by measured antiresonant frequencies. Then, a procedure is proposed for crack identification in cantilever beam by antiresonant frequencies based on the so-called crack scanning method. Theoretical development is illustrated by numerical examples.